Overview of Family Support for Elderly with Hypertension in Kakaskasen 3 and Kakaskasen, Tomohon City, North of Sulawesi - Enggune, Meilita; Nolla Lolowang; Christiane Sarayar; Ebenhaezer Kolinug (Universitas Muhammadiyah Palu, 2025)
Hypertension is one of the most common chronic diseases experienced by the elderly. One key factor in the successful management of hypertension in older adults is family support. Families serve as the entry point in both the prevention and treatment of diseases, as they are the first to recognize early signs of illness, provide health education, and ensure that family members maintain a healthy lifestyle. This study aims to describe the family support for elderly patients with hypertension in Kakaskasen 3 and Kakaskasen, working areas of the Kakaskasen Public Health Center, Tomohon City. This research employed a quantitative descriptive method with purposive sampling. The instrument used was a questionnaire, with a total of 149 respondents. The findings revealed that 67 respondents (44.97%) received good family support, 78 respondents (52.35%) received moderate support, and 4 respondents (2.68%) received poor support. These results indicate that the majority of elderly individuals received moderate support. However, family support should be further optimized so that the elderly feel secure, respected, cared for, and their daily needs are fulfilled. The results of this study are expected to serve as an evaluation material for Kakaskasen Public Health Center to enhance the active role of families in supporting elderly patients with hypertension, through health education, home visits, and continuous assistance.